A novel unibody axial flow pump for the lubrication of inverter type hermetic reciprocating compressors. (August 2022) - Shahzad, Aamir; Pashak, Pouya; Lazoglu, Ismail
Highlights: Solved lubrication problem of an inverter type hermetic compressor at low speed. A unibody axial flow pump has been designed, manufactured, and tested. The pump is capable to provide immediate and sufficient lubrication oil at low speed. CFD analysis was carried out to optimize the design of the pump. Abstract: Lubrication at low speeds is a general problem in the hermetic reciprocating compressors for household refrigerators. The aim of this article is to present a new method using a novel 3D printed unibody axial flow pump for the lubrication oil supply system of an inverter type hermetic reciprocating compressor during a low speed (< 2000 rpm) operation. The system is based on a 3D printed unibody bladeless impeller axial flow pump attached to the bottom end of the vertical rotating crankshaft partially immersed in the oil sump inside hermetic reciprocating compressor sealed casing. A Computational Fluid Dynamics (CFD) simulation besides the experiment is used to simulate the flow inside the pump to calculate the mass flow rate of the lubrication oil and to optimize the helix angle of the pump. Volume of Fluid (VoF) and Multi Reference Frame (MRF) methods are used for modeling the two-phase flow (air and lubrication oil) and rotary domain respectively. The mass flow rate and climbing time of the lubrication oil in the unibody axial pump are analyzed. The results show that the designed pump is capable to supply the lubrication oil at a low speed i.e., 1400 rpm. Moreover, results indicate that the mass flow rate of the lubrication oil increases as the viscosity decreases. The average climbing time is observed to be 1 s at 1400 rpm and 0.4 s at 2000 rpm.